PERANAN PEMBELAJARAN MODELING DALAM MENINGKATKAN KETERAMPILAN BERIBADAH SISWA DI MADRASAH ALIYAH NEGERI (MAN)-3 MEDAN - rahmad jamil (Universitas Islam Negeri Sumatera Utara Medan, 2017)
ABSTRACT The research in the form of this qualitative study was conducted to determine the role of modeling in improving students worship skills at Madrasah Aliyah Negri (MAN) -3 Medan, and has been completed. In particular, the aim is to determine the role of fiqh teachers, teachers of religious local skill lesson,and teachers of extracullicullar guidance in applying learning process modeling in X class and to find out how teachers guidethe skills of students in daily worship. Then to find outthe role of modeling teaching in enhancing the skills of the students’ worship under the guidance of fiqh teachers, teachers of religious local skill lesson, and teachers of extracullicullar guidance and the problems faced by teachers in applying modeling teaching to improve the skills of the students worshipat MAN -3 Medan.The research location is at Madrasah Aliyah Negri (MAN) -3 Medan.The type of research is qualitative research. The subject of this study is teachers of Madrasah Aliyah Negri (MAN) -3 Medan, especially fiqh teachers, teachers of religious local skill lesson, and teachers of extracullicullar guidance, and students who studied at Madrasah Aliyah Negri (MAN) -3 Medan, which is focused on students of class X.The subjects studied were fiqh, religious local skill lesson, and extracullicullar activity From the results of this study also indicate that there has been an increase in the quality if students skills of worship, or worship of students has been good in terms of reading, movement, and the practice carried out by students after teachers in MAN -3 Medan, especially teachers subjects of Fiqh, subject teachers Skills Religion and tutor activities Extracurricular religious field apply the learning modeling to provide facilities for students in understanding and knowing the practice of worship wew performed daily, both religious, outside the madrassa, at home, or in the life of society Keywords: learning modelling, praying skill, the role of fiqh teachers,